Organosulfide-plasticized solid-electrolyte interphase layer enables stable lithium metal anodes for long-cycle lithium-sulfur batteries - Guoxing Li (Nature Portfolio, 2017)
The practical application of lithium metal anodes suffers from the poor Coulombic efficiency and growth of lithium dendrites. Here, the authors report an approach to enable the self-formation of stable and flexible solid-electrolyte interphase layers which serve to address both issues.